Developing social competences of children with Down syndrome by playing - Jędrzejowska, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The subject of this article is a report from a study on the functioning of children with Down syndrome in a pre-school integration group and the rationality of attending kindergarten. During the research, children with Down syndrome in two groups in a kindergarten in Wrocław were observed. The research started with the thesis that play is the basic form of children’s activity, in which, among others, the social competence of children is shaped. The activity most willingly chosen by children during free play were theatrical forms (role playing, puppet theatres, shadow theatres). The research was conducted for nine months; I was a researcher and educator in this kindergarten.